A low-order adaptive engine model for SI–HCCI mode transition control applications with cam switching strategies. (April 2016) - Gorzelic, Patrick; Shingne, Prasad; Martz, Jason; Stefanopoulou, Anna; Sterniak, Jeff; Jiang, Li
This article presents a low-order engine model to support model-based control development for mode transitions between spark ignition (SI) and homogeneous charge compression ignition (HCCI) combustion modes in gasoline engines. The modeling methodology focuses on cam switching mode transition strategies wherein the mode is abruptly changed between SI and recompression HCCI via a switch of the cam lift and phasing. The model is parameterized to a wide range of steady-state data which are selected to include conditions pertinent to cam switching mode transitions. An additional HCCI combustion model parameter is augmented and tuned based on transient data from SI to HCCI mode transitions where the conditions can be significantly outside any contained in the baseline steady-state parameterization. An adaptation routine is given which allows transient data be assimilated in online operation to update the augmented parameter and improve SI–HCCI transition predictions. With the baseline steady-state parameterization and augmented mode transition parameter, the model is shown to reproduce both steady-state data and transient performance output time histories from SI–HCCI transitions with considerable accuracy.